2014
DOI: 10.3109/02713683.2013.877489
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Mesenchymal Stem/Stromal Cells Decreased CCR7+Antigen Presenting Cells in Mice with Corneal Allotransplantation

Abstract: IV hMSCs reduced the activation and migration of CCR7(+) APCs in the cornea and DLNs in allogeneic corneal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“… 43 Our results demonstrate that, during an immune response, MSC inhibit HEV proliferation, activation and elongation in dLNs, thus reducing the recruitment of immune cells. In agreement with our data, homing of dendritic cell to dLNs was reduced in the presence of MSC in several mouse models 44 , 45 and in vitro co-cultures of MSC with endothelial cells downregulated cytokine-induced recruitment of neutrophils and lymphocytes. 46 …”
Section: Discussionsupporting
confidence: 92%
“… 43 Our results demonstrate that, during an immune response, MSC inhibit HEV proliferation, activation and elongation in dLNs, thus reducing the recruitment of immune cells. In agreement with our data, homing of dendritic cell to dLNs was reduced in the presence of MSC in several mouse models 44 , 45 and in vitro co-cultures of MSC with endothelial cells downregulated cytokine-induced recruitment of neutrophils and lymphocytes. 46 …”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported MSC-derived inhibition of CD83, CD80, CD86, and HLA-DR upregulation in DC differentiation assays [ 14 , 82 87 ] and impairment of their migratory ability, both in vitro and in vivo , toward CCL21 [ 88 , 89 ]. In opposition, Berk et al reported that human umbilical cord blood MSC did not inhibit monocyte differentiation into immature DC and supported not only DC maturation but also the migration towards CCL21 [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike injured sites where tissue repair is promoted 84-87,133 and in organ transplant settings where the probability of rejection of transplant tissues is decreased 94,95,103 , the immunosuppressive action of MSCs may result in the suppression of cancer immunity in tumors, enabling cancer cells to escape immune surveillance. As observed in tissue repair processes, MSCs can influence almost all the components of the immune system to attenuate inflammation and control immune response by interfering with various immune phenomena, such as cytokine secretion and the cytotoxicity of T- and NK cells, B-cell maturation and antibody secretion, and APC maturation, activation, and function 102,134,135 .…”
Section: Mscs and Tumor Microenvironmentmentioning
confidence: 99%